A Survey on Students’ Reading Habits at English Education Study Program of PSDKU Maluku Barat Daya - Tiotor, Rosalina Ketrina; Nikijuluw, Renata C. G. V.; Ferdinandus, Mercy (Koli Journal : English Language Education, 2023)
This Study investigates the students’ reading habits at the English Education Study Program of PSDKU Maluku Barat Daya which was done by conducting a survey from 05 October until 04 November 2021. The total number of respondents who participated in this research was 69 respondents by administering questionnaires with 20 questions. The findings showed that the majority of all respondents like reading but at the same time they just read for college purposes. Thus, reading is not a favourite activity they do without concrete reasons. However, the students have pretty good reading habits.